Exploring Shared Understanding and Practices of Experiential Learning Among African Engineering Educators - Kwuimy, Cedrick; Brijmohan, Yashin; Biyela, Precious; Maphosa, Michelle; Rutagangibwa, Vicent (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
The definition, practice, and assessment of experiential learning (EL) globally and within Africa vary significantly across institutions, even within the same country. This inconsistency is largely due to a lack of research focused on educational landmarks shaped by Africa’s unique socio-cultural challenges, technological divides, and financial struggles. Additionally, there is a lack of knowledge on how to structure Afrocentric practices for EL. This research seeks to address the challenges and disparities in the implementation of EL initiatives across African educational contexts. It aims to identify commonly employed methods of EL and explore the shared understanding of EL practices among African engineering educators. Thirty-two participants from seven African countries completed a survey on their understanding and experiences with EL. Responses from nineteen of those participants were discarded due to incompleteness. The remaining thirteen participants, from seven African countries, were divided into two groups: those familiar with and actively using EL, and those familiar with EL but who have not yet used it. The analysis highlights shared practices, perceived impacts, and participants' understanding of EL. The results emphasize the need for future research to harmonize EL practices across Africa.